2014
DOI: 10.3141/2454-12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Level 1 and Level 2 Electric Vehicle Charging Efficiency

Abstract: North American plug-in electric vehicle (EV) sales are projected to grow steadily in the next decade, and EVs are expected to become a significant portion of the vehicle feet. Widespread electrification of personal transport will require coordination between the electricity and transportation sectors. The coordination could include application of electric efficiency incentives that are commonly used in the energy sector for more efficient products, such as energy star appliances. The use of incentives for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Charger efficiency refers to the energy losses as a result of converting the power from AC to DC mode that shows itself as heat. The efficiency of the charger of Opel Ampere EV is estimated around 94% while based on another study [80], in the USA is revealed that efficiency of this EV is around 86.4%. Totally, the charger efficiency is related to the temperature that means by increasing the temperature, the efficiency can be dropped.…”
Section: Battery Degradationmentioning
confidence: 96%
“…Charger efficiency refers to the energy losses as a result of converting the power from AC to DC mode that shows itself as heat. The efficiency of the charger of Opel Ampere EV is estimated around 94% while based on another study [80], in the USA is revealed that efficiency of this EV is around 86.4%. Totally, the charger efficiency is related to the temperature that means by increasing the temperature, the efficiency can be dropped.…”
Section: Battery Degradationmentioning
confidence: 96%
“…For EVs, the electricity use values in Table C7 were multiplied by an emission factor of 0.223 kgCO2e/kWh, based on the average GHG intensity projected over the next 12 years for electricity from U-M's renewable PPA and 60 U.S. Department of Energy and EPA (2020), p. 39. 61 Sears et al (2014).…”
Section: Emission Reductionsmentioning
confidence: 99%